Development of a prototype robot for transportation within industrial environments - Ribeiro, Tiago (2017)
This paper describes the design and development of an autonomous robot for the Robot@Factory league at “Festival Nacional de Robótica 2016”, held in Bragança, Portugal. This paper describes all the hardware and software components developed for a localization and performance of the robot according to the rules. The challenge consists of a table setup that recreates an industrial environment where a robot has to successfully transport boxes from an initial warehouse to the final warehouse. The destination to which the robot has to carry each box, depends on the state of the box, i.e., depending on the box LED color, even though in some cases the robot has to leave the box temporarily in the called processing machines (which are intermediate stations). The most significant innovation feature of this robot prototype consists of the possibility of carrying up to three boxes simultaneously while being able to select which box to drop. This project was developed with great success, since the team managed to reach the 3rd place in the competition.